TRANSYOGI CIBUBUR PEDESTRIAN PATH: CONNECTING CITY AND NATURE - Efrain Brema Latumeten; Reza Fauzi; Nur Intan Simangunsong (Journal of Synergy Landscape, 2024)
Metropolitan cities like Cibubur are increasingly facing complex mobility challenges. In this context, it is important to consider pedestrian routes as an important element in a sustainable transportation system. This study aims to analyze the pedestrian path model in the Transyogi Cibubur area with a focus on safety and accessibility.A field survey method was used to collect data related to pedestrian behavior patterns, pedestrian path infrastructure, and congestion and accident rates. The data were then analyzed using spatial and statistical modeling techniques to identify accident hotspots and pedestrian traffic density.The results showed that pedestrian routes in the Transyogi Cibubur area face a number of challenges, including narrow sidewalks, lack of crossing safety, and inadequate traffic management. The analysis also revealed pedestrian behavior patterns that need to be considered in infrastructure planning.In conclusion, improving the safety and accessibility of pedestrian routes in Transyogi Cibubur requires a comprehensive approach, including expanding sidewalks, improving crossing safety, and providing supporting facilities such as adequate street lighting. Such measures will support safe and convenient pedestrian mobility, and improve the overall quality of life for Cibubur residents.